What can we learn from international literacy surveys? A critical look at the evidence from Britain - Greg Brooks (Universidade do Minho, 2002)
Despite criticisms, interest in the results of international literacy surveys continues, and three such surveys have taken place in the last three years. This paper is an attempt to show just a few of the lessons that can be learnt from the results of such surveys, using data from Britain as illustrations.